ASSIGNMENT OF HYPERFINE-SHIFTED HEME CARBON RESONANCES IN FERRICYTOCHROME B(5) - LEE, KB; KWEON, J; PARK, H (ELSEVIER SCIENCE BV, 1995)
The reverse detection heteronuclear multiple quantum coherence, HMQC, study of native bovine ferricytochrome b(5) has provided the complete assignment of hyperfine shifted resonances of heme carbons attached proton(s). The dominant delocalized pi-spin density to vinyl groups gives rise to contact shifts which have opposite direction for a carbon and its attached proton(s). The most hyperfine shifted C-13 heme signals are mainly generated from 3rd heme pyrrole ring substituents which identifies that the molecular orbital for facile electron transfer is oriented to exposed heme edge. Magnetic/electronic asymmetry of heme induced by two axial His makes spread the hyperfine shifted heme carbon resonances over the range of 280 ppm at 25 degrees C, which mould be the more sensitive probe than those of proton resonances in characterizing the nature of heme electronic structure of ferricytochrome b(5).